Sidelobe Suppression for Multicarrier Signals via Structured Spectral Precoding - Khawar Hussain; R. López-Valcarce; Francesc Rey; Josep Sala; Javier Villares (IEEE Transactions on Communications, 2024)
Reducing the large sidelobes of multicarrier signals is crucial to prevent adjacent channel interference. Spectral precoding is an effective approach toward this goal, at the expense of throughput loss due to precoder redundancy; thus, it is of interest to explore alternative precoder designs with improved performance at lower redundancies. We present a novel precoder which minimizes radiated power within a userselectable frequency region. The structure of the precoding matrix is chosen to allow efficient mitigation of in-band distortion at the receiver by means of iterative and successive interference cancellation, while completely avoiding distortion to protected and pilot subcarriers. By exploiting the low-rank properties of constituent blocks, computational complexity can be significantly reduced with little impact on sidelobe reduction. Simulation results show the benefits of the proposed design, which is particularly effective in redundancy-limited settings targeting high spectral efficiency.
Keywords: mayte; multicarrier communications; OFDM; spectrum shaping

Spectrum Shaping Techniques for Advanced Multicarrier Communication Systems - Khawar Hussain (Universidade de Vigo, 2023)
Mobile communication has evolved from 1G voice-focused systems to 4G data and mobile broadband services, with the exponential increase in mobile data volume and connected devices leading to the development of the Fifth Generation (5G) mobile network. The 5G network is expected to improve key performance indicators such as data rate, massive connectivity, latency, network reliability, and energy efficiency. To meet these requirements, the 5G air interface must be highly flexible, spectrally efficient, reliable, scalable, and energy-efficient. Among various waveforms proposed for the 5G radio interface, CPOFDM was chosen due to its inherent advantages such as robustness to multipath, compatibility with MIMO, low complexity, and high spectral efficiency. However, it suffers from large spectrum sidelobes, peak-to-averagepower- ratio, and sensitivity to synchronization errors. The focus of this thesis is on the large spectrum sidelobes of OFDM that cause high out-ofband radiation resulting in adjacent channel interference. Therefore, reducing spectral leakage to adjacent channels is crucial for efficient spectrum utilization. Numerous techniques for reducing out-of-band radiation (OBR) have been proposed in the literature, each with its advantages and drawbacks. The performance of an OBR reduction technique is not only measured by its ability to suppress out-of-band emission but also by key performance indicators (KPIs) such as computational complexity, spectral efficiency, in-band distortion, and spectrum overshoot. Balancing key performance indicators (KPIs) is crucial when reducing OBR since it typically involves a tradeoff between one or more performance parameters. However, the tradeoffs are not uniform across different OBR reduction techniques. Thus, it is essential to strike a balance between the KPIs to meet the varying requirements of different use-case scenarios. The thesis presents multiple innovative designs for OBR suppression in multicarrier systems to prevent adjacent channel interference. These designs offer the flexibility to select a frequency range through a spectral weighting function that prioritizes certain frequencies. Additionally, the proposed designs are adaptable enough to enable tradeoffs among the aforementioned KPIs to fulfill the diverse requirements of various applications and scenarios. An effective time-domain windowing technique is proposed that that is both effective and simple, and transparent at the receiver. The proposed optimal window design has the flexibility to shape the power spectral density to focus on OBR at the frequency ranges of interest, unlike traditional windowing approaches. Additionally, the design optimizes OBR performance across different frequency regions based on the system’s requirements. The thesis also presents novel frequency-domain spectral precoding approaches that can tradeoff between OBR performance and complexity, which is especially of interest for battery-operated or low-power devices. The proposed design allows for control over the amount of distortion on data subcarriers, which is determined by a user-selectable parameter, and influences receiver complexity. A joint spectral precoding and windowing design is also presented that leverages the advantages of both approaches. By optimizing the precoder and window coefficients to reduce radiated power within a specified frequency range, the design achieves a superior trade-off between out-of-band radiation (OBR), throughput, and complexity compared to using these techniques individually. The results demonstrate the effectiveness of this approach. Finally, the thesis presents memory-based precoding approach to mitigate the issue of large sidelobes. By incorporating memory into the precoder, out-of-band radiation (OBR) performance can be improved without compromising spectral efficiency, albeit at the expense of increased computational complexity. The novel memory-based precoder is designed to minimize the total OBR within a user-defined frequency range. Additionally, this technique enables control over spectral peaks, thereby allowing for flexible OBR levels.

Joint Precoder and Window Design for OFDM Sidelobe Suppression - Khawar Hussain; R. López-Valcarce (IEEE Communications Letters, 2022)
Spectral precoding and windowing are two effective approaches to reduce out-of-band radiation (OBR) in multicarrier systems. Their performance comes at the price of reduced throughput and additional computational complexity, so there is strong motivation for simultaneously using both techniques. We present a novel design that jointly optimizes the precoder and window coefficients to minimize radiated power within a user-selectable frequency region. Results show that the proposed design achieves a better OBR/throughput/complexity tradeoff than either of these individual techniques separately.
Keywords: rodin; spectrum shaping

Orthogonal precoding with memory for sidelobe suppression in OFDM - Khawar Hussain; R. López-Valcarce (European Signal Processing Conference (EUSIPCO), 2022)
Orthogonal precoding is a very effective approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. This is achieved at the cost of introducing precoder redundancy, which results in throughput loss. Introducing memory in the precoding operation has the potential to improve performance without sacrificing additional spectral efficiency, in exchange for extra computational complexity. We present a novel orthogonal memory precoder which minimizes OBR within a user-selectable frequency region and allows for controlling spectral overshoot. Decision-feedback decoding avoids symbol error rate degradation at the receiver.
Keywords: rodin; spectrum shaping

Mask-Compliant Orthogonal Precoding for Spectrally Efficient OFDM - Ravinder Kumar; Khawar Hussain; R. López-Valcarce (IEEE Transactions on Communications, 2021)
Orthogonal precoding constitutes a powerful technique to reduce spectrum sidelobes of multicarrier signals. This reduction is bought at the cost of introducing precoder redundancy, which results in some throughput loss and additional precoding/decoding complexity. When the goal is to meet some spectral emission mask constraints, it is desirable to avoid unnecessary sidelobe suppression in order to keep precoder redundancy at a minimum. In this context, we introduce a general framework under which we develop a novel Lagrange multiplier-based mask-compliant orthogonal precoder design targeting minimal redundancy. We also adapt to this framework two previously proposed designs based on spectral notches and minimum out-of-band emission, respectively, to explicitly incorporate mask constraints. Simulation results are provided to show the effectiveness of the proposed designs under different practical masks for multicarrier wireless systems.
Keywords: rodin; spectrum shaping; winter

Memory Tricks: Improving Active Interference Cancellation for Out-of-Band power reduction in OFDM - Khawar Hussain; R. López-Valcarce (IEEE Int. Workshop Signal Process. Adv. Wireless Commun. (SPAWC), 2021)
Although active interference cancellation (AIC) is an appealing approach to reduce out-of-band radiation (OBR) in multicarrier systems without distorting data subcarriers, it usually requires a large number of reserved subcarriers to be effective. Introducing memory in AIC precoding may help alleviate this drawback in exchange for some increase in computational complexity. We propose a novel memory AIC precoder which, in contrast to previous schemes, minimizes OBR within a user-selectable frequency region and allows for controlling spectral overshoot.
Keywords: rodin; spectrum shaping

Optimal window design for W-OFDM - Khawar Hussain; R. López-Valcarce (IEEE Int. Conf. Acoustics, Speech and Signal Processing (ICASSP), 2020)
Windowing is an effective approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. However, commonly used window functions are chosen in an ad hoc manner and fixed. We present an optimal window design for windowed-OFDM minimizing OBR within a given frequency region. The proposed technique is flexible in that it allows to specify the range of frequencies involved in the minimization and to apply spectral weighting. The optimal window can be computed offline.
Keywords: spectrum shaping; winter

Flexible spectral precoding for OFDM systems - Khawar Hussain; R. López-Valcarce (2nd XoveTIC Conference, 2019)
Spectral precoding is a popular approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. However, it introduces distortion in the data, appropriate decoding is required at the receiver side. Thus, trading off between implementation complexity, OBR reduction and error rate is important. We present a novel linear precoder design with flexibility to trade off OBR reduction, precoding/decoding complexity, and error rate at the receiver. Moreover, the constraint can be imposed on each subcarrier individually to provide more flexibility. The precoding matrices have low rank, which translates into significant computational savings. In this way, the requirements of different systems can be satisfied with varying complexity levels
Keywords: spectrum shaping; winter

Flexible spectral precoding for sidelobe suppression in OFDM systems - Khawar Hussain; Ana Lojo; R. López-Valcarce (IEEE Int. Conf. Acoustics, Speech and Signal Processing (ICASSP), 2019)
Spectral precoding is a popular approach to reduce out-of-band radiation (OBR) in multicarrier systems in order to avoid adjacent channel interference. Since precoding will introduce signal distortion, appropriate decoding is required at the receiver side. We present a novel linear precoder design with flexibility to trade off OBR reduction, precoding/decoding complexity, and error rate at the receiver. The precoding matrices have low rank, which translates into significant computational savings. In this way, the requirements of different systems can be satisfied with varying complexity levels.
Keywords: spectrum shaping; winter

OFDM spectral precoding with per-subcarrier distortion constraints - Khawar Hussain; R. López-Valcarce (European Signal Processing Conference (EUSIPCO), 2019)
Spectral precoding is effective in reducing out-of-band radiation (OBR) in multicarrier systems, but it introduces distortion in the data, requiring a suitable decoder at the receiver. Thus, trading off OBR reduction, implementation complexity, and error rate is of paramount importance. We present a precoder design which minimizes OBR under constraints on the distortion at each individual data subcarrier. By judiciously choosing the distortion profile, the decoding task can be significantly alleviated, with a sizable improvement in terms of implementation complexity with respect to previous designs.
Keywords: spectrum shaping; winter